Molecular characterisation of the NAM-1 genes in bread wheat in Australia - Yang, R.; Juhasz, A.; Zhang, Y.; Chen, X.; Zhang, Y.; She, M.; Zhang, J.; Maddern, R.; Edwards, I.; Diepeveen, Dean; Islam, S.; Ma, W. (CSIRO Publishing, 2018)
The wheat NAM-B1 and NAM-A1 genes are positively associated with grain protein content (GPC) in wheat. We conducted molecular characterisation of the NAM-1 genes in 51 Australian wheat varieties (Triticum aestivum L.), with the aim of improving GPC and nitrogen-usage efficiency in Australian wheat. In summary, the wild type NAM-B1 gene, which originated from Israel, was identified in two Australian wheat varieties. Five varieties contained a deletion allele, whereas the majority (43) harboured a non-functional NAM-B1 allele and one variety contained both functional and non-functional alleles. Twenty-six Australian wheat varieties contained the NAM-A1a haplotype, which was similar to its well-characterised homoeolog NAM-B1 wild type and associated with high GPC. The NAM-D1 gene in the 51 wheat varieties was also characterised, and no gene variation in the exon regions was noted; only two single-nucleotide polymorphisms in introns 1 and 2 were found among the 51 varieties.